Determining Micro Banking Together with The Development of Financial Technology in The New Normal Era - Ni Made Pipin Indah Pratiwi; I Gusti Ngurah Putra Suryanata (Institute of Computer Science (IOCS), 2020)
The financial sector is one of the business sectors that has undergone significant changes, known as Financial Technology (FinTech). FinTech is here to answer the problem of public financial access to conventional financial institutions. The development of non-bank financial institutions in rural areas has greatly helped rural communities to increase rural economic growth. The LPD functions as a container of village wealth in the form of money or letters, carries out its function in the form of efforts towards improving the standard of living of village manners and in its business activities supports a lot of village development. This study aims to determine the strategies used by the Lembaga Perkreditan Desa (LPD) in supporting implementation financial technology in the middle of the New Normal Era and to find out the impact felt by the community by its implementation financial technology in the middle of the New Normal Era. The method used in this research is a qualitative approach with sample selection purposive sampling. In this study, the process of data collection and processing was assisted by using the SWOT matrix which is a tool used to compile the company's strategic factors. Strategies that can support the implementation of financial technology LPD Talepud and LPD Ketewel provide a sense of comfort, security, and convenience in making transactions using LPD Mobile. Customers who use LPD Mobile can experience practicality, such as withdrawals via LPD ATMs, electricity payments, credit purchases, quota purchases, PDAM payments, BPJS payments and others.